Causal relationship between PCSK9 inhibitor and common neurodegenerative diseases: A drug target Mendelian randomization study - Qiang Huang; Qin Zhang; Bei Cao (Brain and Behavior, 2024)
Abstract Background In addition to lowering cholesterol levels, the proprotein convertase subtilis kexin 9 (PCSK9) inhibitor has a variety of effects, including anti‐neuroapoptosis. However, the effects of PCSK9 inhibitors on neurodegenerative diseases are controversial. Therefore, we used drug‐targeted Mendelian randomization (MR) analysis to investigate the effects of PCSK9 inhibitors on different neurodegenerative diseases. Methods We collected single nucleotide polymorphisms (SNPs) of PCSK9 from published statistics of genome‐wide association studies and performed drug target MR analyses to detect a causal relationship between PCSK9 inhibitors and the risk of neurodegenerative diseases. We utilized the effects of 3‐Hydroxy ‐3‐ methylglutaryl‐assisted enzyme A reductase (HMGCR) inhibitors (statin targets) for comparison with PCSK9 inhibitors. Coronary heart disease risk was used as a positive control, and primary outcomes included amyotrophic lateral sclerosis (ALS), Parkinson's disease (PD), and Alzheimer's disease (AD). Results PCSK9 inhibitors marginally reduced the risk of ALS (OR [95%] = 0.89 [0.77 to 1.00], p = 0.048), while they increased the risk of PD (OR [95%] = 1.417 [1.178 to 1.657], p = 0.004). However, HMGCR inhibitors increased the risk of PD (OR [95%] = 1.907 [1.502 to 2.312], p = 0.001). Conclusion PCSK9 inhibitors significantly reduce the risk of ALS but increase the risk of PD. HMGCR inhibitors may be the risk factor for PD.